Factors influencing brand awareness of feminine hygiene products among young female adults / Rohani Jangga... [et al.] - Jangga, Rohani; M Ali, Norlina; Shahwir, Siti Farrah; Ali, Alizah; Ab Rani, Nur Hanani (UiTM Cawangan Johor, 2019)
This paper studied the effects of distribution, pricing, advertising and brand activationon brand awareness among young female adults. Data from 100 respondents were analyzed using descriptive, correlation and multiple regression analysis. Empirical results authenticated that brand activation significantly affects brand awareness. Input regarding the effects of distribution, price, advertising and brand activation on brand awareness among respondents would be crucial in helping marketers formulate strategies to enhance their brand, obtain competitive advantage and business sustainability among young consumer markets. Empirical findings offer academic contributions to the existing body of knowledge of consumer behavior. The findings indicated price and advertising as significant towards brand awareness.